Origin of lead associated with different reactive phases in Scottish upland soils: an assessment made using sequential extraction and isotope analysis - Bacon, Jeffrey R.; Hewitt, Irene J.; Cooper, Patricia (Journal of environmental monitoring, 2004)
Soil samples (0-25 cm) have been taken annually since 1991 from three protected plots set up at an upland location at Glensaugh in Aberdeenshire, Scotland. The soils were analysed using the original BCR sequential extraction procedure and the lead isotopic composition was determined in each of the fractions, as well as the unfractionated soil using thermal ionisation mass spectrometry (TIMS). The lead concentrations in all the soils, including those well away from the road, were much higher than typical background values indicating that the whole area has been subject to deposition of anthropogenic lead. The distribution of lead between the different fractions was similar for the two non-roadside soils with most lead present in the oxidizable fraction. Although most lead in the roadside soil was also present in the oxidizable fraction, a substantial proportion (about 10%) was in the easily soluble fraction suggesting that roadside lead could be more mobile than lead in the other soils. Good reproducibility was obtained for the isotope analyses in all the fractions. The ratios calculated for the bulk soil from the ratios in the individual fractions agreed very closely with those measured directly in the unfractionated soil thereby demonstrating both reproducibilty and accuracy. The lowest (206)Pb/(207)Pb ratios were found in the roadside soil consistent with the recent deposition of petrol lead. The (206)Pb/(207)Pb ratios in all fractions of the other soils fell into a narrow band and it was necessary to use (204)Pb ratios to differentiate between lead in the extractable fractions and lead in the residual component. It is probable that lead in the non-roadside soils was deposited a considerable time ago and is characterised by a relatively high (206)Pb/(207)Pb ratio. Use of the (204)Pb ratios showed that the residual components in each of the three soils were isotopically distinct.